Alcohol consumption does not increase the risk of surgical wound complications in breast cancer patients - de Menezes, Raquel Ferreira (Int Wound J, 2020)
Alcohol consumption, despite influencing several organic processes, has been scarcely studied regarding the risk of developing surgical wound complications after surgical breast cancer treatment. The aim of this study was to analyse the association between alcohol consumption and the development of surgical wound complications in women undergoing surgical treatment for breast cancer. A prospective cohort study was conducted, comprising 486 women between 40 and 69 years old, interviewed during the preoperative period and followed up for 30 days. The occurrence of seroma, necrosis, surgical site infection (SSI), dehiscence, ecchymosis, and hematoma were considered as outcomes. Alcohol consumption during the 30 days prior to surgery was reported by 20.8% of the patients, with 8.4% being occasional consumers and 12.4% regular consumers. Binge drinking was reported by 10.2% of the women. The presence of surgical wound complications was observed in 65.2%. The most frequent complications were seroma (54.3%), necrosis (17.7%), and SSI (7.8%). No statistically significant association between alcohol consumption and the development of cicatricial complications was observed.